Streptococcus pyogenes carriage rate, associated factors and antimicrobial susceptibility profiles among urban and rural schoolchildren at Gondar city, Northwest Ethiopia - Yalewayker Gashaw; Alem Getaneh; Desie Kasew; Mitkie Tigabie; Baye Gelaw (Scientific Reports)
Abstract Streptococcus pyogenes remains one of the top ten causes of mortality from infectious diseases. Children in low-income nations have high carrier rates of Streptococcus pyogenes, which can serve as a source of infections, including simple superficial infections that may lead to invasive and post-streptococcal diseases, particularly among schoolchildren. This study aimed to assess the prevalence of Streptococcus pyogenes, associated factors, and antimicrobial susceptibility profiles among urban and rural public schoolchildren in Gondar City, Northwest Ethiopia. A school-based comparative cross-sectional study was conducted via a multistage sampling technique among elementary schoolchildren from April to June 2022 in Gondar City. Sociodemographic and clinical data were collected via a pretested structured questionnaire. Standard microbiological methods were used to collect and process throat swabs to isolate Streptococcus pyogenes. An antimicrobial susceptibility test was performed via the disk diffusion method. Epi-Info version 7.2.5 was used to enter the data, which were then exported to SPSS version 25 for analysis. Logistic regression analysis was used to determine the strength of associations between variables, and p < 0.05 was considered statistically significant. The overall prevalence of Streptococcus pyogenes in 438 children was 11.2% (n = 49), with 71.43% (35/49) being urban and 28.57% (14/49) being rural. Low-income parents, hospital admission history, and cigarette smoking in the home were found to be substantially linked with Streptococcus pyogenes carriage among students (p < 0.05). All the Streptococcus pyogenes isolates were susceptible (100%) to penicillin and cefotaxime, but 18.8% and 12.25% of the isolates were resistant to amoxicillin and tetracycline, respectively. The prevalence of Streptococcus pyogenes throat carriage among was intermediate. All the isolates were sensitive to penicillin and cefotaxime, but 18.8% and 12.25% of the isolates were resistant to amoxicillin and tetracycline, respectively. Thus, regular screening and surveillance of Streptococcus pyogenes among schoolchildren should be conducted to minimize carriage or infections and maintain the rational use of antimicrobials. Health education about cigarette smoking in the house also needs to be provided to and the community.